Intra-sectoral structural change and aggregate productivity development: a robust stochastic nonparametric frontier function approach - Jens J. Krüger (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
This paper investigates the sources of total factor productivity growth in the German manufacturing sector, 1981-1998. Decomposition formulae for aggregate productivity growth are used to identify the effects of structural change and entry-exit on aggregate productivity growth. Documented is a substantial rise of productivity growth after the German reunification. The bulk of this rise can be attributed to structural change and entry-exit. Two methodological refinements are implemented, the first is the application of a robust stochastic nonparametric approach to frontier function analysis and the second is the calculation of bootstrap confidence intervals for the components of the productivity decompositions.
Keywords: D24; O12; L60; 330; Productivity decomposition; structural change; manufacturing; Produktivität; Industrieller Strukturwandel; Dekompositionsverfahren; Technische Effizienz; Nichtparametrisches Verfahren; Verarbeitendes Gewerbe; Schätzung; Deutschland